La medición de la autoestima en adolescentes y adultos: una propuesta desde el modelo de Harris Clemens - Cerna Dorregaray, Orlando (2017)
While research on self-esteem measurement is extensive and it is a variable related to others such as aggression, academic performance, and school success or failure, we have observed that the theoretical foundations and instruments used in most studies are largely the same. For example, research conducted with children and adolescents in the last ten years has been based on the theoretical proposals of Branden, Milicic, and Misitu, and has used scales such as those of Rosenberg and Coopersmith. In our own studies, we had the opportunity to learn about an important and different theoretical proposal that has been useful in explaining self-esteem in children and its relationship, for example, to school success. This is Harris Clemens's (1998) proposal on self-esteem. Clemens argues that self-esteem is the satisfaction we feel with ourselves when we have been able to satisfy four basic needs: belonging, uniqueness, power, and standards.